Enhanced attentional processing during speech perception in adult high-functioning autism spectrum disorder: An ERP-study. (15th October 2021) - Borgolte, Anna; Roy, Mandy; Sinke, Christopher; Wiswede, Daniel; Stephan, Michael; Bleich, Stefan; Münte, Thomas F.; Szycik, Gregor R.
Abstract: Deficits in audiovisual speech perception have consistently been detected in patients with Autism Spectrum Disorder (ASD). Especially for patients with a highly functional subtype of ASD, it remains uncertain whether these deficits and underlying neural mechanisms persist into adulthood. Research indicates differences in audiovisual speech processing between ASD and healthy controls (HC) in the auditory cortex. The temporal dynamics of these differences still need to be characterized. Thus, in the present study we examined 14 adult subjects with high-functioning ASD and 15 adult HC while they viewed visual (lip movements) and auditory (voice) speech information that was either superimposed by white noise (condition 1) or not (condition 2). Subject's performance was quantified by measuring stimulus comprehension. In addition, event-related brain potentials (ERPs) were recorded. Results demonstrated worse speech comprehension for ASD subjects compared to HC under noisy conditions. Moreover, ERP-analysis revealed significantly higher P2 amplitudes over parietal electrodes for ASD subjects compared to HC. Highlights: Audiovisual speech perception deficts in a high-functional type of autism spectrum disorders (ASD) persist into adulthood P2 enhancement for participants with high-functioning ASD is irrespective of background noise Enhancement of attentional processes in participants with high-functioning ASD as compensatory mechanism